Career adapt-abilities among technical and vocational education students in colleges of education, Nigeria - Ebenehi, Amos Shaibu (2016)
This study sought to understand the relationship between vocational identity, career future concern, personal goal orientation, perceived social support, career self-efficacy, and career adapt-abilities, and also the significant predictors of career adapt-abilities among technical and vocational education (TVE) students in colleges of education in Nigeria respectively. The study used 603 TVE students from six randomly selected colleges of education in Nigeria. The selected TVE students, who cut across all the three levels of the TVE program of the colleges, were drawn from agricultural, business, and technical education course majors. Correlational research design was used for the study. A set of self-reported structured questionnaire was used for data collection through direct administration of the instrument on the participants by the researcher. Descriptive statistics (frequencies, percentages, mean, and standard deviations), as well as, inferential statistics were used to analyze the data, based on the research questions, and hypotheses of the study. The findings of the study revealed that the mean scores of male TVE students were higher than those of the females in vocational identity, career future concern, personal goal orientation, career self-efficacy, and career adapt-abilities, but, females scored higher than males in perceived social support. The findings indicated that the relationship between vocational identity, personal goal orientation, perceived social support, career self-efficacy, and career adapt-abilities among TVE students was in each case positively significant with substantial strength of relationship. The findings also showed that personal goal orientation, and career self-efficacy were significant predictors of career adapt-abilities among TVE students in colleges of education in Nigeria. On the other hand, vocational identity, and perceived social support were not significant predictors of career adapt-abilities among the TVE students. However, all the predictors collectively accounted for a reasonable variance of the total variance in career adapt-abilities among TVE students in colleges of education in Nigeria. Furthermore, the findings indicated that, there was a direct mediation effect of career self-efficacy on the relationship between personal orientation and career adapt-abilities among TVE students in colleges of education in Nigeria. The study suggested that TVE managers, educators, and counselors should provide career adapt-abilities awareness and enhancement programs using especially, the measures of personal goal orientation, perceived social support, and career self-efficacy, to enrich career adapt-abilities among their students. In addition, special career orientation program, trips to industries, flexible and creative projects, career public lectures, problem solving techniques, and career interactive forum through innovative instructions, research, and counselling services should be encouraged and sponsored by the management of TVE colleges to enhance career adapt-abilities among the students. The management of the TVE colleges should provide adequate career adapt-abilities resources for students’ career exploration, and make it a policy to ensure proper monitoring of the career adaptabilities progress of their students through regular assessment exercise from their point of entry into the colleges to the time of their graduation from the colleges. Proper monitoring will help the management to plan relevant career adapt-abilities intervention programs for the TVE students. Suggestions were also made for further studies on career adapt-abilities.